1998
DOI: 10.1002/(sici)1097-0045(19980215)34:3<214::aid-pros9>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Induction of atypical prostatic hyperplasia in rats by sympathomimetic stimulation

Abstract: BACKGROUND Prostatic innervation may participate in its homeostasis and growth. α‐Adrenergic inhibition alleviates clinical symptoms in benign prostatic hyperplasia. However, the prostatic effect of adrenergic agonists has not been investigated. This study deals with the prostatic effect of subchronic sympathomimetic stimulation. METHODS Male rats received daily subcutaneous injections of the α‐adrenergic agonist phenylephrine, 1, 10, or 20 mg/kg per day, the β‐adrenergic agonist isoproterenol, 1, 2.5 or 5 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…Following ligation of the spermatic cord and vessels, testes and epididymis were removed. The remaining stump was pushed back through the inguinal canal into the abdominal cavity, and the scrotal sac was closed by sutures [23]. After castration, the rats were maintained under standard laboratory conditions for 7 days in order to allow a definite involution of the prostatic gland [24].…”
Section: Methodsmentioning
confidence: 99%
“…Following ligation of the spermatic cord and vessels, testes and epididymis were removed. The remaining stump was pushed back through the inguinal canal into the abdominal cavity, and the scrotal sac was closed by sutures [23]. After castration, the rats were maintained under standard laboratory conditions for 7 days in order to allow a definite involution of the prostatic gland [24].…”
Section: Methodsmentioning
confidence: 99%
“…These lesions were noted to intensify over time. Likewise, Golomb et al [18] showed that phenylephrine, an α-adrenergic agonist that induces hypertension, also induces atypical glandular BPH in treated rats. It remains to be explained why systemic vascular dysfunctions might specifically affect the prostate gland, a question that may be better answered with more research into the vascular system of the human prostate gland.…”
Section: Hypoxia and Prostate Cells: Potential For Cell Growth Stimulmentioning
confidence: 99%
“…Previous studies showed that phenylephrine treatment induced atypical prostatic hyperplasia and mild fibrosis in the rat ventral prostate (Golomb et al, 1998;Rosenzweig et al, 2004;Rosenzweig-Bublil and Abramovici, 2006). These effects have been related to a tissue repair process occurring subsequent to the inflammatory exudates that takes place during early period of phenylephrine treatment.…”
Section: Discussionmentioning
confidence: 97%